Framing of Female Leading Roles in Drama Series on Video Streaming Platforms - Soliman, Manatalah (AUC Knowledge Fountain, 2021)
This comparative study examines the female-centered drama series aired on VOD services from three different genres. While several studies have established the stereotypical representation of women in the drama series, most research has focused on individual countries. The significance of this study relies upon the fact that the series is from VOD services, notably Netflix and Shahid VIP. The study bridges a gap in the literature by adopting a comparative perspective to analyze gender portrayals from six drama series, three from each country, from three genres. The contemporary drama genre included Valeria from Spain and Leh Laa?! Why Not?! from Egypt. Historical drama genre included Cable Girls ‘Las Chicas Del Cable’ from Spain and Grand Hotel ‘Secrets of The Nile’ from Egypt. And from the crime/thriller drama genre Locked up ‘Vis a vis’ from Spain and Fe Koul Osboua Youm Gomaa ‘Every week on Friday’ from Egypt. This study utilizes a content analysis method over the entire population of the six series, six leading female characters analyzed. A total of 153 episodes were analyzed, resulting in 5,883 scenes for the female actors coded. Various research studies from different countries demonstrate that women are portrayed negatively, sexualized, and shown in traditional female stereotypes and roles such as weak, emotional, nonprofessionals, and housekeepers (Signorielli and Bacue, 1999; Abdelfattah, 2015; Atwan, 2006). Findings here revealed that women continue to be portrayed negatively in drama series across both countries and that stereotypical patterns continue to dominate the drama series. However, this study noted significant differences among countries.